(untitled) (Research, Society and Development, 2019)
The present article aims to present a literature review aimed at the understanding of the term interdisciplinarity and the practice of the teacher as an object of research. We sought to understand the meaning of the term interdisciplinarity from the readings of the following theoreticians: Japiassu, Fazenda and Pombo. Having as research subjects a group of teachers. Seeking to understand the social representations of the same ones about the interdisciplinary practice directed to the Teaching of Sciences in the schools of the Municipality of Volta Redonda / RJ. The methodology used was qualitative research, having a semistructured questionnaire as a data collection instrument, applied to the said group acting in the Initial Years of Elementary Education. In the analysis of the data the Bardin Thematic Categorical Analysis was used. The research showed that there is a mistaken understanding by the teachers about the term interdisciplinarity thus interfering in their interdisciplinary practice.